El desarrollo de la sociología jurídica latinoamericana - Silva García, Germán; Nicole Velasco Cano, Jairo Vladimir Llano Franco,; Vizcaíno Solano, Angélica (Opción, 2020)
Con influencia europea la sociología jurídica nace en Latinoamérica, para avanzar por tres etapas. En la primera, coincide con las críticas al positivismo jurídico; en la segunda, las contribuciones esclarecen el objeto de estudio y sus fundamentos teóricos y metodológicos; por último, es forjado un ambiente maduro para su progreso. Entre los países donde alcanza un mayor desarrollo se encuentran Argentina, Brasil, Colombia, México y Venezuela. Este trabajo demostrará que la sociología jurídica latinoamericana ha adquirido una identidad y desarrollos singulares, lo que ha revertido de manera natural en una defensa de los derechos humanos y fundamentales.  AbstractLegal sociology was born in Latin America significantly influenced by European authors and thought, and has since undergone three stages. In the beginning it embraced a critical outlook of legal positivism; in a next phase, attention was focused on the clarification of the object of study, as well as the theoretical and methodological foundations of legal sociology; more recently, the field has forged a mature environment for its continuing advancement. Major developments are observed mainly in Argentina, Brazil, Colombia, Mexico and Venezuela. This article contends that in this process, Latin American legal sociology has treaded a singular path towards its present identity and developments, and has naturally reverted to the defense of human and fundamental rights